The Involvement of Uric Acid in the Pathogenesis of Preeclampsia - Masoura, Sophia; Makedou, Kali; Theodoridis, Theodoros; Kourtis, Anargyros; Zepiridis, Leonidas; Athanasiadis, Apostolos (Current Hypertension Reviews, 2015)
Preeclampsia is a common disorder of human pregnancy and a major cause of worldwide pregnancy-related maternal and neonatal morbidity and mortality. Oxidative stress, angiogenic imbalance, placental ischemia and an inflammatory response have been proposed to play role in the pathogenesis of the disease. Hyperuricemia is a key biochemical feature in preeclampsia with elevated levels of uric acid being diagnosed as early as the 10th week of gestation. Traditionally, elevated uric acid levels were considered a result of renal dysfunction known to exist in preeclampsia. The contribution of uric acid in the pathogenesis of preeclampsia is being recently further investigated. We, hereby, review the possible mechanisms by which uric acid contributes to the development of the disease and its complications both on mother and fetus.
Keywords: Antioxidant